2020
DOI: 10.3390/ijerph17176159
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Self-Harm Following Hospital-Presenting Intentional Drug Overdose among Young People—A National Registry Study

Abstract: Background: The incidence of hospital-presenting self-harm peaks among young people, who most often engage in intentional drug overdose (IDO). The risk of self-harm repetition is high among young people and switching methods between self-harm episodes is common. However, little is known about their patterns of repetition and switching following IDO. This study aimed to investigate repeat self-harm and method-switching following hospital-presenting IDO among young people. Methods: Data from the National Self-Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Of the 69 (30.4%) patients connected with the social care service team (of 227 patients total), only 21(30.4%) agreed to follow ups, and only 11 completed case management a total of four times or reconnected to other social care service teams, while others refused or could not participate in postaccident care. Several studies have reported that the mortality and recurrence rate of suicide signi cantly decreased in patients who underwent follow-up care compared with those who did not [17,20]. Thus, because the prospective study design does not include long term output, mortality would increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 69 (30.4%) patients connected with the social care service team (of 227 patients total), only 21(30.4%) agreed to follow ups, and only 11 completed case management a total of four times or reconnected to other social care service teams, while others refused or could not participate in postaccident care. Several studies have reported that the mortality and recurrence rate of suicide signi cantly decreased in patients who underwent follow-up care compared with those who did not [17,20]. Thus, because the prospective study design does not include long term output, mortality would increase.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies distinguished between different types of drugs and found that speci c drugs carried higher risks. Additionally, young adults tend to acquire over-the-counter drugs because many other drugs are not easily acquired [20]. Thus, future studies should consider kinds and amounts of drugs based upon adolescents' characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, switching to more lethal methods is a predictor of completed suicide in adults (adjusted hazard ratio, 7.05) 5) . In patients aged 10-24 years with DI, those aged 10-17 years have a 1.3-fold higher risk of repeated self-harm than those aged 18-24 years 6) . Despite the lower severity of suicidal intention and the overuse of over-the-counter medicine in adolescents 7) , their higher rate of repetition of SAs may lead to fatal outcomes.…”
Section: Introductionmentioning
confidence: 94%
“…Neither changes in the type of drugs in adolescents with DI nor those in the intensity or anatomical region in patients with cutting was regarded as changes in the methods. DI was defined as all types and amounts of potentially lethal drugs whereas previous studies distinguished between different types of drugs and found that specific drugs carried higher risks 6) . The meaningful SA defined above was the primary outcome.…”
Section: Variables Of Interestmentioning
confidence: 99%